Analysis and Discussion on Emergency Rescue Inspection Case of Machine Roomless Elevator by Data. Issue 1 (1st February 2023) - Wang, Lei
Abstract: This paper introduces the principle and method of emergency rescue for machine room-less elevator, analyzes an inspection case due to the failure of the electric release function, studies and proposes the importance of monitoring the door lock signal by the electric release device through the electrical working principle, and analyzes the failure reason and safety hidden danger of the emergency rescue device for machine room-less elevator.